Determinan Produktivitas Tenaga Kerja Industri Manufaktur Besar dan Sedang di Pulau Sumatera - Windy Dwi Astutik; Siti Aisyah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Labor productivity is actually a comparison of output or output with all the resources used or in this case it is called input whose function is to increase economic growth. This research has a mission to provide estimates of the direction and magnitude of the determinants of life expectancy, the average duration of schooling, and also the minimum wage of a province along with the human development index on the labor productivity of large and medium manufacturing industries on the island of Sumatra in the period 2018 to 2020 by applying panel data regression. The findings from this research then show that life expectancy has a positive effect, meanwhile, the provincial minimum wage has a negative effect on labor productivity. Meanwhile, it is known that the average duration of schooling and the human development index are not determinants of labor productivity in large and medium manufacturing industries in the same year. Local governments in each province in Sumatra are expected to be able to provide special attention to the education and health sectors. In the context of increasing in the education and health sectors, this will also have implications for the quality of workers who will also improve so that the implication is being able to increase production output and expectations will be determined at the level of economic growth.